Integrated fertilizer management impact on soil chemical properties, growth and yield of orange-fleshed sweet potato (ipomoea batatas (l) lam) at Ikwo, Ebonyi State, Nigeria - Susan, Iroegbu Chidinma; Uzoma, Izuogu Chibuzo; Chukwudindu, Iroegbu Cornelius; Kelechi, Eluagu; Nnadozie, Onwunmelu Wisdom (International Journal of Sustainable Agricultural Research, 2025)
A field experiment was conducted at Alex Ekwueme Federal University Teaching and Research Farm, Ndufu-Alike, Ebonyi State, Nigeria, in the 2022 planting season to evaluate the impact of integrated fertilizer on soil chemical characteristics, growth, and yield of orange-fleshed sweet potato (OFSP). The treatments comprised Rice Mill Waste (RMW) applied at 0, 2, 4, and 6 tons/ha and Nitrogen 27: Phosphorus 13: Potassium 13 (NPK 27:13:13) fertilizer applied at 0, 200, 400, and 600 kg/ha, which were combined to produce 16 treatment combinations with three replicates in a Randomized Complete Block Design (RCBD). All the data collected were subjected to the analysis of variance (ANOVA) using the GENSTAT software package, and the treatment means were separated using Fisher’s Least Significant Difference (LSD) at a 5% level of probability. The findings of the study demonstrated that the amended plots showed improvements in soil chemical characteristics as well as the growth and yield parameters of Orange Fleshed Sweet Potato (OFSP) over the control. The application of amendment at the rate of 6t/ha RMW + 600kg/ha NPK produced the best results. The combination of RMW and NPK fertilizer significantly (P<0.05) improved soil chemical properties like pH, available phosphorus, soil organic carbon, total nitrogen, soil exchangeable properties, and increased OFSP growth and yield components like the number of branches, vine length, number of leaves, and yield of OFSP. The integration of both organic and inorganic fertilizer materials could enhance the growth and yield of OFSP as well as the nutrient level of the soil.